The Dao of the sceptic and the spiritual: attitudinal and cultural influences on preferences for sustainable tourism services in the domestic Chinese tourism market. (10th March 2010) - Barkmann, Jan; Yan, Jiong; Zschiegner, Anne-Kathrin; Marggraf, Rainer
The study assesses Chinese tourist preferences for southwest China destination attributes – including the availability of sustainable tourism services (STS). Using the choice experiment method, the influence of attitudinal variables and of cultural values on preferences is also estimated. Data are collected from 213 middle class respondents in Beijing and Chengdu. STS is the only destination attribute which has no clear influence on destination choice. Factor analysis singled out two 'positive' attitudinal dimensions (in favour of sustainability, concern for losing future opportunities) and one 'negative' dimension (sceptical attitude on STS). Only the sceptical attitude on STS significantly influenced destination choice, and substantially reduced willingness-to-pay (WTP) for STS. Based on images of nature analysis of cultural values by factor analysis, robustness by divine designer and a non-spirituality dimension displayed substantial impacts on destination preferences. The less spiritual the images of nature of a Chinese middle class tourist, the less s/he prefers – and is willing to pay for – trips featuring more natural attractions and more STS.